Supply Chain Management Analysis on Plumbing Works - Nuciferani, Felicia Tria; Aulady, Mohamad Ferdaus Noor; Wardani, Milla Kusuma; Ardiyanto, Nanang (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
One of the methods of applying lean construction in the construction sector that shifts from traditional to lean, eliminating all activities that do not generate added value, is supply chain management. This research compares the supply chain in two projects to decide on added value projects. This stems from the efficiency of establishing a simple organizational structure and encouraging contractors to focus more on the dominant material work. Supply Chain is a systems approach to delivering products to end consumers by using information technology and coordinating with suppliers and manufacturers/producers. The supply chain comparison for the second project is more inclined to the project apartment because it has four patterns and does not have much organizational coordination. In the apartment project pattern, the main contractor focuses on the project's core and provides activities to support subcontractors, such as elevator work. MEP work on buildings is complex, especially in coordinating the procurement of equipment, materials, and human resources because it involves many people and organizations both from outside and in the implementation process. Supply chain management in the construction sector is an effort to improve performance. To be more effective and efficient in providing high competitiveness for other contractor companies. Supply chain management in the construction sector is an effort to improve performance. To be more effective and efficient in delivering high competitiveness for other contractor companies. Supply chain management in the construction sector is an effort to improve performance.